Impact of short‐term Dutasteride treatment on prostate‐specific membrane antigen expression in a mouse xenograft model. Issue 6 (19th May 2021) - Kranzbühler, Benedikt; Sousa, Rosa; Prause, Lukas; Burger, Irene A.; Rupp, Niels J.; Sulser, Tullio; Salemi, Souzan; Eberli, Daniel
Abstract: Background: Dutasteride has been shown to increase expression of the prostate‐specific membrane antigen (PSMA) in prostate cancer cells in previous in vitro studies. This 5‐alpha‐reductase inhibitor is commonly used for the treatment of symptomatic benign prostatic enlargement. The modulation of PSMA expression might affect PSMA‐based prostate cancer imaging and therapy. Aim: The purpose of this work was to further analyze concentration‐dependent effects of Dutasteride on PSMA expression in a mouse xenograft model. Methods and results: Four groups of mice bearing LNCaP xenografts were treated for 14 days with daily intraperitoneal injections of either vehicle control or different concentrations of Dutasteride (0.1, 1, 10 mg/kg). Total expression of PSMA, androgen receptor (AR), and caspase‐3 protein was analyzed using immunoblotting (WES). In addition, PSMA, cleaved caspase‐3 and Ki‐67 expression was assessed and quantified by immunohistochemistry. Tumor size was measured by caliper on day 7 and 14, tumor weight was assessed following tissue harvesting. The mean PSMA protein expression in mice increased significantly after treatment with 1 mg/kg (10‐fold) or 10 mg/kg (sixfold) of Dutasteride compared to vehicle control. The mean fluorescence intensity significantly increased by daily injections of 0.1 mg/kg Dutasteride (1.6‐fold) as well as 1 and 10 mg/kg Dutasteride (twofold). While the reduction in tumor volume following treatment with high concentrations of 10 mg/kg Dutasteride was nonsignificant, no changes in AR, caspase‐3, cleaved caspase‐3, and Ki‐67 expression were observed. Conclusion: Short‐term Dutasteride treatments with concentrations of 1 and 10 mg/kg significantly increase the total PSMA protein expression in a mouse LNCaP xenograft model. PSMA fluorescence intensity increases significantly even using lower daily concentrations of 0.1 mg/kg Dutasteride. Further investigations are needed to elucidate the impact of Dutasteride treatment on PSMA expression in patients.